PENGEMBANGAN VIDEO PEMBELAJARAN LAJU REAKSI BERBASIS STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) PADA MATA PELAJARAN KIMIA KELAS XI IPA - Zahra Assyfa Yusri; Kuntum Khaira (Journal of Chemistry Education and Integration, 2023)
This research is based on the lack of activity of students in the learning process, the learning process is carried out only centered on the teacher and the media used by the teacher is only in the form of power points that have not been developed, so that students are less interested in the learning process. The purpose of this study was to develop STAD (Student Teams Achievement Division) based learning videos and determine the level of validity and practicality. This study uses the Research and Development (R&D) method with a 4-D development model which includes 4 phases, including: Define, Design, Development, Disseminate. This research was carried out up to the third stage including: 1) At the Define stage, it was carried out to get an overview of the conditions in the field, 2) at the Design stage, it was carried out to design STAD (Student Teams Achievement Division) based learning videos, 3) at the Development stage This is followed by validity and practicality testing. The test subjects in this study were students of class XI MIPA-2 SMAN 1 West Sumatra. The results of the study show that: 1) STAD (Student Teams Achievement Division) based learning videos have met the valid criteria with a validation result of 89.28%. 2) the developed STAD (Student Teams Achievement Division)-based learning videos have met practical criteria with 83.75% student questionnaire results and 77.5% teacher questionnaires. The results of this study indicate that the developed STAD (Student Teams Achievement Division) based learning videos can be used as learning media for teachers and students in learning. Keywords: Learning Videos, STAD (Student Teams Achievement Division), Laju Reaksi